Gender Mainstreaming Toolkit for the Space Sector - United Nations Office for Outer Space Affairs (United Nations, 2024)
Space4Women is an initiative of the United Nations Office for Outer Space Affairs (UNOOSA) to advance gender equality in the space sector and in the STEM fields. The objectives of Space4Women are to raise awareness about the importance of gender equality and women’s empowerment in the space sector; to strengthen and deliver targeted capacity building activities both at institutional and individual level; to encourage women and girls to pursue space and STEM education and careers; and to contribute to achieving Sustainable Development Goal (SDG) 4 on quality education and SDG 5 on gender equality. The Toolkit is a comprehensive resource that addresses a range of challenges, and its ultimate goal is not inherently utopian – it is, in the end, enshrined in the Charter of the United Nations.